Crowdfunding Syariah dan E-Wallet sebagai Alat Penggerak UMKM - Adlan Ali (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The development of the Sharia-based digital economy in Indonesia is showing significant dynamics, particularly through innovations in crowdfunding and Sharia-compliant e-wallets. This phenomenon not only reflects advances in financial technology but also serves as a strategic instrument in driving the growth of Micro, Small, and Medium Enterprises (MSMEs). However, accelerating this innovation requires legal certainty that aligns with Sharia principles and consumer protection. This study aims to analyze the regulatory framework governing crowdfunding and Sharia-compliant e-wallets, examine the role of Bank Indonesia and the Financial Services Authority (OJK) in overseeing their implementation, and identify challenges and opportunities in the legal politics of the Sharia economy in the digital era. The method used is normative research with a legislative and conceptual approach, complemented by analysis of secondary data in the form of regulations, fatwas, and recent academic literature. The study results indicate that the synergy between national regulations and Sharia principles is the main foundation for maintaining a balance between innovation and legal compliance. Furthermore, the existence of adaptive regulations and responsive oversight by financial authorities are key to strengthening public trust in the Sharia-compliant digital economy ecosystem.